Corporate Governance and Legal Compliance in State Owned Banks - Hasnah Aziz; Dhian Tyas Untari; Firman Maulana; Ahmad Syarif; Nyayu Maya Ardini (Cita Konsultindo Research Center, 2026)
This paper examines the relationship between corporate governance practices and legal compliance in state-owned banks. It focuses on how governance structures, including board oversight, transparency, and accountability mechanisms, influence the ability of these institutions to comply with regulatory requirements. The study highlights the unique challenges faced by state-owned banks, such as political influence, dual objectives of profitability and public service, and complex stakeholder environments. It argues that strong corporate governance frameworks play a critical role in ensuring consistent legal compliance and reducing risks associated with mismanagement and regulatory breaches. Furthermore, the paper provides insights into how improving governance standards can enhance institutional credibility, financial stability, and public trust. The findings underscore the importance of aligning governance practices with legal obligations to strengthen the overall performance and sustainability of state-owned banks.